Sink or Float: Experiencing Distance Learning Education through the Lens of College Students - Kitongan, Vivian Grace L; Gutierrez, Joselito C (Asian Journal of Education and Training, 2022)
At the onset of pandemic, schools offer online classes for those who have access to internet and correspondence-based learning (CBL) for those who have difficulties accessing internet signal. Hence, this study delved into the learning experiences of college students who subscribed to the CBL modality. Using phenomenology design, findings showed the difficulties and good experiences encountered in the CBL platform. Difficulties referred as sinkers are learning environment difficulty, scaffolding shortage and mental struggles. Good experiences referred as floaters are family bond support, mentor support, and dependent support. After two years of having this distance learning format, students still experience difficulties that pull them from achieving quality education. However, there are still good things out of these experiences which push them achieve their educational goals. This study hopes to contribute in advancing curriculum design, planning, and implementation of distance learning education, particularly those using solely modules in the Philippine education setting.